Beyond COVID-19 Pandemic: Changes in Interaction Pattern between Children and Caregivers - Karademir, Abdulhamit (BILGE AKADEMIK YAYINCILIK EGITIM BILISIM VE DANISMANLIK HIZMETLERI, 2021)
We are going through hard times that remind us that good health is the most important thing in life. The COVID-19 pandemic has immensely affected everybody. Measures taken by all countries, including Turkey, to prevent the spread of the coronavirus have deprived students (from preschool to university) of face-to-face education. While the pandemic has had a profound impact on parents and educators, children's lives have been stuck between the “new normal” and the pandemic. This paper investigated how children and their parents experienced the pandemic, how they interacted, and managed educational activities at home. This was a case study, which is a qualitative research method. The sample consisted of 15 families with different sociocultural and socioeconomic status (SES) living in five cities in four regions of Turkey. Data were collected through video-audio recordings, observation notes, and e-interviews. Data were analyzed using second-cycle coding and inductive content analysis. The COVID-19 pandemic caused economic problems, especially in low- and middle-SES families. Economic problems and mental stress impeded the marital interaction patterns of couples, negatively affecting children the most. Upper-SES parents received support from teachers for homeschooling, but other parents faced numerous setbacks and made numerous errors during home-based education, causing parents despair and concern for their children's future. Of all participants, the children of the parents with COVID-19 related health problems were affected by outbreak measures the most. These results can help raise all stakeholders' awareness of the current situation. Given that the COVID-19 pandemic may continue for the foreseeable future, it is believed that the suggestions made to parents and educators for homeschooling can help mitigate the future impacts of the pandemic, especially on preschoolers.
Keywords: Other Fields of Education; Alan Egitimleri